2014
DOI: 10.1007/s10853-014-8783-1
|View full text |Cite
|
Sign up to set email alerts
|

On ball-milled ODS ferritic steel recrystallization: From as-milled powder particles to consolidated state

Abstract: International audienceRecrystallization of a ball-milled ferritic ODS steel is studied towards its evolution from as-milled powder to consolidated state. This characterization has been made possible by using a combination of X-ray Diffraction (XRD) and an innovative method based on an Automated Crystallographic Orientation Mapping (ACOM) tool attached to a Transmission Electron Microscope (TEM). Focus Ion Beam preparation has been essential to obtain a thin section of the ODS steel powder particle and perform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Taking the fusion zone in the heat-treated joint (Table 1) as an example, the grain size distribution has two peaks at 1.42 and 7.20 µm, respectively, as can be seen in Figure 7. Similar bimodal grain size distributions have been widely reported for powder metallurgy-prepared ODS steels [18][19][20]. In martensitic-ferritic steels, which generally contain 0.1-0.2 wt% C and 9-11 wt% Cr [21], this phenomenon could be due to the dual phase nature of the material.…”
Section: Microstructure Characterisationsupporting
confidence: 79%
See 2 more Smart Citations
“…Taking the fusion zone in the heat-treated joint (Table 1) as an example, the grain size distribution has two peaks at 1.42 and 7.20 µm, respectively, as can be seen in Figure 7. Similar bimodal grain size distributions have been widely reported for powder metallurgy-prepared ODS steels [18][19][20]. In martensitic-ferritic steels, which generally contain 0.1-0.2 wt% C and 9-11 wt% Cr [21], this phenomenon could be due to the dual phase nature of the material.…”
Section: Microstructure Characterisationsupporting
confidence: 79%
“…Meanwhile, in the heat-treated condition, the KAM is smaller than that of the as-joined condition and shows no significant difference in different regions, demonstrating that the microstructure is substantially recovered and homogenous after the normalising and tempering treatment, which would be beneficial for the mechanical properties. [18][19][20]. In martensitic-ferritic steels, which generally contain 0.1-0.2 wt% C and 9-11 wt% Cr [21], this phenomenon could be due to the dual phase nature of the material.…”
Section: Microstructure Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…As at high temperatures the fine grain structure can be a drawback in terms of creep resistance, the bimodal grain size distribution is a compromise between a creep resistant coarse microstructure and radiation resistant fine‐grained material with high strength at lower temperatures . The following effects were found to contribute to the formation of a nonuniform grain structure in ODS steels: (1) a nonuniform distribution of oxide particles leading to a spatial variation in the pinning force, (2) inhomogeneous temperature distribution during sintering or (3) an inhomogeneous dislocation density after MA, leading to a variation in the driving force for recrystallization.…”
Section: Introductionmentioning
confidence: 99%
“…This means that TEM methods can sometimes only be used to calculate the Kernel average misorientation in a region and not the full dislocation density (Sallez et al, 2015;Nzogang et al, 2018) or when it is possible (for high dislocation densities in deformed materials) they tend to over-estimate the dislocation density as small rotations are 'rounded up' as described previously. Despite this, initial studies on cold-worked pure metals have found comparable results to dislocation densities determined by other means (Ghamarian et al, 2014).…”
Section: Plastic Deformation and Dislocationsmentioning
confidence: 99%